Anti-urolithiatic terpenoid compound from Plantago major Linn. (Ekor Anjing) - Sharifa A.A.; Jamilah Jamaludin; Kiong L.S.; Chia L.A.; Osman K. (2024)
The aim of this study was to determine the inhibition effects of the terpenoid of Plantago major on calcium oxalate crystals in vitro and to compare the effects of Plantago major with clinically used drugs like zyloric and potassium citrate for the treatment of urinary stone. Modified Schneider slide gel method was used for in vitro study and crystals formed were measured by Image Analyser System (Leica) after 24 h of treatment. The active compound in the methanol extract of Plantago major was isolated by bioassay - guided fractionation & isolation method. Dimethylsulphoxide (DMSO) was used as the negative control and zyloric and potassium citrate were used as positive controls. The results showed that crude methanol extract of Plantago major contained the active compound terpenoid. Terpenoid, zyloric and potassium citrate at concentrations in the range of (100 ?g/mL - 250 ?g/mL) signifcantly inhibited the area of crystal formation in comparison to the negative control after 24 h (p<0.001). The Zyloric and terpenoid of Plantago major in the concentrations of (100 ?g/mL-250 ?g/mL) inhibited the sizes of crystals signifcantly (p<0.05). Potassium citrate was more effective, than terpenoid of Plantago major in inhibiting the size of crystals at two concentrations i.e. 100 ?g/mL and 150 ?g/mL respectively (p<0.05). However the IC 50 values for terpenoid of Plantago major, potassium citrate and zyloric were 250 ?g/mL, 300 ?g/mL and 550 ?g/mL, respectively. The inhibition effect of the terpenoid of Plantago major extract on crystal size was much better than Zyloric and potassium citrate.